2017
DOI: 10.1111/cbdd.13136
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, biological evaluation, and docking study of 4‐isochromanone hybrids bearing N‐benzyl pyridinium moiety as dual binding site acetylcholinesterase inhibitors (part II)

Abstract: A series of novel 4-isochromanone compounds bearing N-benzyl pyridinium moiety were designed and synthesized as acetylcholinesterase (AChE) inhibitors. The biological evaluation showed that most of the target compounds exhibited potent inhibitory activities against AChE. Among them, compound 1q possessed the strongest anti-AChE activity with an IC value of 0.15 nm and high AChE/BuChE selectivity (SI > 5,000). Moreover, compound 1q had low toxicity in normal nerve cells and was relatively stable in rat plasma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…In addition to this, docking studies carried out on XJP-1 showed a dual-binding property for both the PAS and CAS of the AChE enzyme ( Wang et al, 2015 ), which may further justify the low dosage needed to slow down the amyloid aggregation, since the PAS of AChE has been linked to increased amyloid-β peptide aggregation rate ( Inestrosa et al, 1996 ). Despite not being tested in this study, XJP-1 has been predicted to have anti-inflammatory and anti-oxidant properties due to its natural product-derived structure, which may have also played a role in ameliorating the AD symptomatology in Aβ arc flies ( Wang et al, 2015 , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this, docking studies carried out on XJP-1 showed a dual-binding property for both the PAS and CAS of the AChE enzyme ( Wang et al, 2015 ), which may further justify the low dosage needed to slow down the amyloid aggregation, since the PAS of AChE has been linked to increased amyloid-β peptide aggregation rate ( Inestrosa et al, 1996 ). Despite not being tested in this study, XJP-1 has been predicted to have anti-inflammatory and anti-oxidant properties due to its natural product-derived structure, which may have also played a role in ameliorating the AD symptomatology in Aβ arc flies ( Wang et al, 2015 , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Following extensive previous in vitro studies, here we present biological evaluation of our previously reported novel AChE inhibitor (Wang et al, 2015), named XJP-1, using the Aβ arc Drosophila AD model. XJP-1 is a naturally derived product, with part of the structure derived from a compound isolated in the peel of Musa sapientum L., which has shown an excellent inhibitory activity against AChE, along with a high specificity for AChE over butyrylcholinesterase (BuChE) (Wang et al, 2015(Wang et al, , 2018. In addition to this, XJP-1 was predicted to have high BBB permeability in docking studies and no toxicity on neurotypic SH-SY5Y cells (Wang et al, 2015(Wang et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…To a solution of 2-bromo-4,5-dimethoxybenzaldehyde ( 1 ) (81.61 mmol, 1 eq) in 100 mL methanol, sodium borohydride (40.80 mmol, 0.5 eq) was slowly added at 0 °C and the mixture was stirred at the same temperature. After the completion of the reaction was detected by TLC, crushed ice was added into the mixture and stirred for another 1 h. After filtration, the filtrate was washed with cold water and collected as a white solid [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…The combined organic layers were washed with brine (200 mL) and dried over anhydrous Na 2 SO 4 . The organic layers were removed in vacuo to give crude colorless oil 3 [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation